2015
DOI: 10.1111/mpp.12327
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia activates pacC and patulin accumulation in an acidic environment during apple colonization by Penicillium expansum

Abstract: Penicillium expansum, the causal agent of blue mould rot, causes severe post-harvest fruit maceration simultaneously with the secretion of d-gluconic acid (GLA) and the mycotoxin patulin in colonized tissue. The factor(s) inducing patulin biosynthesis during colonization of the host acidic environment is unclear. During the colonization of apple fruit in vivo and growth in culture, P. expansum secretes pH-modulating GLA and ammonia. Although patulin and its possible opportunistic precursor GLA accumulate toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 53 publications
11
61
1
Order By: Relevance
“…We further found that the PacC 3 could be detected at pH 5.0-8.0 (Fig. 1D), confirming the result that the Pal pathway is already active at low pH (4.5-5.0) in P. expansum (Barad et al, 2016). In addition, the PacC 3 was not detected at pH 3.0-4.0 and the cleavage efficiency increased with the rise of ambient pH (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We further found that the PacC 3 could be detected at pH 5.0-8.0 (Fig. 1D), confirming the result that the Pal pathway is already active at low pH (4.5-5.0) in P. expansum (Barad et al, 2016). In addition, the PacC 3 was not detected at pH 3.0-4.0 and the cleavage efficiency increased with the rise of ambient pH (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…In A. nidulans , the full‐length PacC polypeptide is processed by two successive proteolytic cleavages and yields a shorter, functional PacC at alkaline pH (Orejas et al ., ). In P. expansum‐21 , EMSA and supershift analysis have showed that the PePacC is not fully protected against proteolytic signalling at pH 4.5 relative to pH 7.0 (Barad et al ., ). Here, pH shift experiments with Flag 3 ::PacC strain straightly showed the presence of three truncated versions of PePacC (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This raises the possibility that regulation occurred through the zinc finger protein denoted PacC, involved in the regulation of pHcontrolled genes in filamentous fungi (Peñalva et al, 2008). PacC activates transcription of those pathogenicity factors depending on the environmental pH in several host-pathogen interactions (Alkan et al, 2013;Barad et al, 2016). All these differences among the members of RG-HYDs family would provide the fungus with versatile and complementary tools for degrading substrates under different conditions during degradation of the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…The pacC gene has also been found in several other postharvest fungal pathogens and contributes to the full virulence of these pathogens, including Colletotrichum gloeosporioides (Alkan et al, 2013); P. expansum (Barad et al, 2014); and P. digitatum (Zhang et al, 2013). In P. expansum, ambient pH and pacC are also involved in the secondary metabolism and have been shown to affect the production of the mycotoxin patulin (Barad et al, 2015;Zong et al, 2015). Although there are conflicting reports on the possible role of this mycotoxin in pathogenesis (Ballester et al, 2015;Barad et.…”
Section: Cinereamentioning
confidence: 99%